Pelaksanaan Penyidikan dalam Perkara Tindak Pidana Pencurian di Polres Indragiri Hilir (Studi Perkara Nomor: LP/B/41/VII/2025/SPKT/Polres Inhil) - Marhat; Vivi Arfiani Siregar; Kms Novyar Satriawan F (Indragiri Law Review, 2025)
This study aims to analyze the implementation of criminal investigation in theft cases at the Indragiri Hilir Resort Police based on Case Number: LP/B/41/VII/2025/SPKT/POLRES INHIL, and to identify the obstacles encountered by investigators during the investigation process. This research employed an empirical legal research method with a descriptive-analytical approach using both normative juridical and empirical juridical perspectives. Data were collected through interviews, observations, and library research, then analyzed qualitatively using a deductive method. The findings indicate that the investigation process has been conducted in accordance with the Indonesian Criminal Procedure Code and Law Number 2 of 2002 concerning the Indonesian National Police, including report reception, preliminary inquiry, formal investigation, examination of witnesses and suspects, collection of evidence, and submission of case files to the public prosecutor. The main obstacles include limited human resources, inadequate facilities, difficulties in obtaining witness statements, limited evidence, and geographical conditions. These obstacles are addressed through enhanced coordination, optimization of available resources, and strengthened cooperation with the community and related institutions to improve the effectiveness of criminal investigations.